THE EFFECTIVENESS OF THE RECONSTRUCTION OF RESIDENTIAL BUILDINGS (International Conference on Medical Science, Medicine and Public Health, 2025)
The reconstruction of residential buildings is an integral part of urban regeneration, addressing various challenges posed by aging infrastructure, outdated designs, and increasing urban populations. As cities evolve, older residential structures often fail to meet contemporary safety standards, energy efficiency needs, and the changing demands of modern living. The effectiveness of residential building reconstruction lies in its ability to rejuvenate these buildings while enhancing structural integrity, improving energy efficiency, and aligning them with modern sustainability practices. This article explores the key drivers behind successful residential reconstruction projects, including advancements in technology, sustainability initiatives, and modern safety standards. It also highlights the challenges that hinder reconstruction projects, such as financial constraints, regulatory issues, and the integration of innovative technologies. By examining these aspects, the article demonstrates how the reconstruction of residential buildings can have a significant positive impact on urban communities, improving not only the quality of life for residents but also the broader environmental and economic sustainability of cities[5].